2021
DOI: 10.1101/2021.05.21.445234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plant pathogenic bacterium can rapidly evolve tolerance to an antimicrobial plant allelochemical

Abstract: Crop losses to plant pathogens are a growing threat to global food security, and hence, more effective control strategies are urgently required. Biofumigation, an agricultural technique, where Brassica plant tissues are mulched into soils to release antimicrobial plant allelochemicals called isothiocyanates (ITCs), has been proposed as an environmentally friendly alternative to synthetic agrochemicals. While biofumigation has been shown to suppress a range of plant pathogens, its effects on plant pathogenic ba… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 100 publications
0
2
0
Order By: Relevance
“…These findings supported previous analyses of RSSC IS which identified disruptions in type III effectors (26) and in the global virulence regulator phcA (27), the latter of which resulted in spontaneous phenotypic conversion between non-virulent and virulent pathogen genotypes. It was also recently shown that RSSC IS are highly mobile under lab conditions and may contribute to host competitiveness and environmental stress tolerance (28). However, thus far our understanding of IS in RSSC is based on experimental studies of individual strains (27,28) and a small number of genomes derived from publicly available databases (29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings supported previous analyses of RSSC IS which identified disruptions in type III effectors (26) and in the global virulence regulator phcA (27), the latter of which resulted in spontaneous phenotypic conversion between non-virulent and virulent pathogen genotypes. It was also recently shown that RSSC IS are highly mobile under lab conditions and may contribute to host competitiveness and environmental stress tolerance (28). However, thus far our understanding of IS in RSSC is based on experimental studies of individual strains (27,28) and a small number of genomes derived from publicly available databases (29).…”
Section: Introductionmentioning
confidence: 99%
“…It was also recently shown that RSSC IS are highly mobile under lab conditions and may contribute to host competitiveness and environmental stress tolerance (28). However, thus far our understanding of IS in RSSC is based on experimental studies of individual strains (27,28) and a small number of genomes derived from publicly available databases (29). As a result, the wider diversity and distribution of IS in RSSC is unknown.…”
Section: Introductionmentioning
confidence: 99%